The Effect of Work Discipline, Work Motivation, and Work Performance Communication on Employees - Pakpahan, Simon Ryansa Hasudungan; Simanjorang , Jurisman; Pratiwi , Devi Arista; Siahaan, Lidia Sari; Girsang, Patrecia Caroline; Sitorus, Sunday Ade; SUNDAY ADE SITORUS (Lembaga Riset Ilmiah, 2023)
With it discipline, motivation, and good communication at work is part very influential on the performance of employees. This research intends to find out the results of variable discipline work, motivation work, and communication Work on performance employees on PT. Meganusa Semesta, Medan. In-process data study This uses SPSS. Study A uses the method quantitative and approach the study uses approach descriptive, with the technique of Simple Random sampling, the researcher can determine the sample with use formula Slovin. In the present study, it was found population a number of 77 meanwhile the sample a total of 43 employees. The test results reveal that in a manner Partial variable discipline work is not influential and significant the performance employees at PT. Meganusa Semesta, Medan. Whereas variable motivation Work as well as communication Work own influence positive and significant on the performance employees at PT. Meganusa Semesta, Medan. Test results simultaneous showing that the performance of employee is influenced in a way Which same by compensation discipline work, motivation work and communication work at the same time. So can be concluded that discipline work, motivation work, as well communication very work influence will the performance of employee.